2015
DOI: 10.4037/ajcc2016728
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Diagnosis of Sepsis: Polymerase Chain Reaction System Versus Blood Cultures

Abstract: Objective To compare the utility of a multiplex polymerase chain reaction system (SeptiFast) and blood cultures for detecting bacteria and fungi in blood samples from patients with severe sepsis or septic shock. Methods In a prospective observational study, whole blood samples for SeptiFast testing and for culture were collected on admission from all patients with severe sepsis or septic shock admitted to the intensive care unit between July 2011 and September 2012. SeptiFast results were compared with blood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
(70 reference statements)
2
11
1
Order By: Relevance
“…In this respect our data are in line with studies [22, 38] that demonstrated a higher rate of positivity of SF for the treated group with the difference, however, not reaching statistical significance. A significant difference has been reported in other studies [4244]. …”
Section: Discussioncontrasting
confidence: 81%
“…In this respect our data are in line with studies [22, 38] that demonstrated a higher rate of positivity of SF for the treated group with the difference, however, not reaching statistical significance. A significant difference has been reported in other studies [4244]. …”
Section: Discussioncontrasting
confidence: 81%
“…34 To detect bacteraemia, culture methods are needed, but they are time-consuming and often give false-negative results or the results may only indicate microbial contamination. 35 As in most previous studies, in the present study, PCT had a better diagnostic capacity than CRP to predict complicated course of febrile neutropenia. 29,36 Meidani et al 36 Sensitivity and specificity in ROC curve analysis for patients who developed sepsis was higher for PCT (92.5% and 97.3%, respectively).…”
Section: Discussionsupporting
confidence: 76%
“…Blood and/or TLF culture were performed to detect bacteria and fungi. To detect and differentiate up to 25 pathogenic microbial DNAs in blood samples, the LightCycler SeptiFast Test (Roche Diagnostics GmbH, Manheim, Germany) was used …”
Section: Methodsmentioning
confidence: 99%